Note bibliographique - Hannick, Jean-Marie (Les Lettres Romanes, 2013)
Abstract Pierre Bayle, Correspondance. Tome IX : janvier 1693-mars 1696. Lettres 902-1099. Publiées et annotées par Élisabeth Labrousse (†) et Antony McKenna, Laurence Bergon, Hubert Bost, Wiep Van Bunge, Edward James, Annie Leroux, Bruno Roche, Caroline Verdier, Fabienne Vial-Bonacci, avec la collaboration d’Éric- Olivier Lochard. Oxford, Voltaire Foundation, 2012